A Novel Strategy for the Microbial Removal of Heavy Metals: Cell-surface Display of Peptides - Wang, Yuanyuan; Selvamani, Vidhya; Yoo, Ik-Keun; Kim, Tae Wan; Hong, Soon Ho (Biotechnology and bioprocess engineering, 2021)
Cell surface engineering is a rapidly developing technology of microorganism that achieves modification of cell surface function by joining external functional peptides with surface anchoring proteins, for example, Outer Member Protein (OMP). On account of these proteins possessing metal responsive motifs, they can be specifically used for metal adsorption and dissociation. To elucidate the problems caused by heavy metals and develop various technologies for their removel or recovery, various metal-binding proteins/peptides fused on microorganism cell surface have been applied as novel methods. During the past few years, bacterial cell surface display strategy has received growing attention for their availability to eliminate heavy metals. In this paper, the existing problems, progress, and suggestions for furture of the peptide displaying system are summarized.